Estimating fractional cover of plant functional types in African savannah from harmonic analysis of MODIS time-series data. Issue 9 (3rd May 2018) - Ibrahim, Sa'ad; Balzter, Heiko; Tansey, Kevin; Tsutsumida, Narumasa; Mathieu, Renaud
ABSTRACT: Assessments of tree/grass fractional cover in savannahs using remote sensing are challenging due to the heterogeneous mixture of the two plant functional types. Time-series decomposition models can be used to characterize vegetation phenology from satellite data, but have rarely been used for attributing phenological signal components to different plant functional types. Here, tree/grass dynamics are assessed in savannah ecosystems using time-series decomposition of 14 years of Moderate Resolution Imaging Spectroradiometer (MODIS) normalized difference vegetation index data acquired from 2002 to 2015. The decomposition method uses harmonic analysis and tests the individual harmonic terms for statistical significance. Field data of fractional cover of trees and grasses were collected for 28 plots in Kruger National Park, South Africa. Matching MODIS pixels were analysed for their tree/grass phenological signals. Tree/grass annual and interannual variability were then assessed based on the harmonic models. In most harmonic cycles, grass-dominated sites had higher amplitudes than tree-dominated sites, while the tree green-up started earlier than grasses, before the start of the wet season. While changes in tree phenology are gradual, grasses present higher variability over time. Tree cover showed a significant correlation with the amplitude ( r (correlation coefficient) = −0.59, p  = 0.001) and phase of the first harmonic term ( r  = −0.73, p  = 0.0001) and the number of cycles of the second harmonic term ( r  = 0. 56, p  = 0.002). Grass cover was also significantly correlated with the amplitude ( r  = 0. 51, p  = 0.005) and phase of the first harmonic term ( r  = 0.55, p  = 0.002) and the number of cycles of the second harmonic term ( r  = −0.52, p  = 0.005). The positive correlation of grass cover with phase and negative correlation with number of cycles is indicating a late greening period and higher variability, respectively. Tree cover estimated from the phase of the strongest harmonic term showed a positive correlation with field-measured tree cover ( R 2 (coefficient of determination) = 0.55, p  < 0.01, slope = 0.93, root mean square error = 13.26%). The estimated tree cover also had a strong correlation with the woody cover map ( r  = 0.78, p  < 0.01) produced by Bucini. The results show that MODIS time-series data can be used to estimate the fractional tree cover in heterogeneous savannahs from the phase of the plant functional type's phenological behaviour. This study shows that harmonic analysis is able to discriminate between fractional cover by trees and grasses in savannahs. The quantitative analysis of tree/grass phenology from satellite time-series data enables a better understanding of the dynamics of the tree/grass competition and coexistence.